Three-Dimensionally Printed Personalized Implant Design and Reconstructive Surgery for a Bone Tumor of the Calcaneus: A Case Report. Issue 2 (April 2018) - Park, Jong Woong; Kang, Hyun Guy; Lim, Kwun Mook; Kim, June Hyuk; Kim, Han Soo
Abstract : Case: A 23-year-old soldier was diagnosed with a calcaneal desmoplastic fibroma. Limb-salvage surgery using a 3-dimensionally (3D) printed personalized implant made from a titanium alloy was planned. The implant had a mesh-style surface for free tendon suture, and the joint surface was smooth to preserve the subtalar joint. The implant had 3 hollow posts in case of future transarticular immobilization. At the last follow-up, the implant was painless and stable, and the patient could walk normally without support. Conclusion: A 3D-printed personalized implant showed acceptable functional and anatomic outcomes for a calcaneal bone tumor. Appropriate design modification of a 3D-printed personalized implant enabled an optimal outcome in our patient.